2021
DOI: 10.1002/dc.24815
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic features of malignant rhabdoid tumor of the liver: A case report and literature review

Abstract: As one of the SMARCB1‐deficient tumors, malignant rhabdoid tumor (MRT) of the liver is a rare and aggressive malignancy, typically in young children below the age of 3 years. The diagnosis of MRT of the liver is challenging both clinically and pathologically due to the rarity of the tumor and misdiagnosing it as a hepatoblastoma is not uncommon. Although MRT of the liver and hepatoblastoma share some similar clinical and morphological features, their prognosis and the clinical management are significantly diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Around 76% of the patients had metastatic disease at presentation, with lungs and lymph nodes being the most common sites of metastasis. 8,14 The current patient had respiratory distress at presentation, and a chest X-ray revealed lung metastasis.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Around 76% of the patients had metastatic disease at presentation, with lungs and lymph nodes being the most common sites of metastasis. 8,14 The current patient had respiratory distress at presentation, and a chest X-ray revealed lung metastasis.…”
Section: Discussionmentioning
confidence: 88%
“…2,3 MRT of the liver is exceptionally infrequent and accounts for less than 5% of all pediatric hepatic malignancies. 5,8,17 The clinicopathological findings are limited to few case reports and series due to the rarity of this entity. A series of six cases of hepatic MRT by Cornet et al revealed a median age of presentation of 5 months, which is similar to the current case.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations